Analisis political uncertainty dan non-performing loan pada bank non devisa di Indonesia - Ali Jufri; Rista Puput Aryanti; Desy Ayu Krisna Murti; Bhenu Artha (Universitas Widya Mataram, 2021)
This study aims to determine the differences in non-performing loans (NPLs) at non-foreign exchange banks in Indonesia for the two-year period before and after the general election. The results showed that there was no difference of non-performing loans (NPLs) at non-foreign exchange banks in Indonesia for the period of two years before and after the general election.